Analysis Of Capital Market Reaction Before And After The 17 + 8 Demands Demonstration Of September 1, 2025 (An Event Study On Bank Central Asia) - Andi Putri Ainun (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The Indonesian capital market is highly sensitive to socio-political events that generate uncertainty and influence investor behavior. This study examines the capital market reaction to the 17 + 8 Demands Demonstration held on September 1, 2025, using Bank Central Asia (BCA) as the object of analysis. Employing an event study methodology, this research analyzes differences in Average Abnormal Return (AAR), Cumulative Abnormal Return (CAR), and trading activity before and after the event. The market model is used to estimate expected returns, with an event window of (-10, +10) trading days surrounding the demonstration date. Statistical analyses, including normality tests and t-tests, are applied to assess the significance of market reactions. The findings reveal a shift in investor sentiment, where AAR and CAR change from positive values before the event to negative values afterward, indicating increased uncertainty following the demonstration. Although these changes are not statistically significant, the observed return and trading volume patterns suggest short-term market adjustments to publicly available information. Overall, the results support the semi-strong form of the Efficient Market Hypothesis, indicating that the Indonesian capital market responds rapidly to socio-political events while exhibiting temporary inefficiencies and volatility. These findings provide important implications for investors and regulators in managing risks associated with political uncertainty.